2009
DOI: 10.7213/cienciaanimal.v7i1.8906
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Fisiológico De Estrobilurina F 500® No Crescimento E Rendimento Do Feijoeiro

Abstract: O objetivo do trabalho foi o de avaliar os efeitos fisiológicos da estrobilurina F 500® no crescimento e rendimento do feijoeiro. O trabalho experimental de campo foi conduzido na Fazenda Experimental Gralha Azul (FEGA) da Pontifícia Universidade Católica do Paraná (PUCPR), no ano agrícola de 2006. O experimento foi implantado em uma área sob plantio direto, utilizando-se um delineamento experimental de blocos ao acaso com oito tratamentos de quatro repetições. Os tratamentos testados foram: testemunha absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 0 publications
1
16
0
11
Order By: Relevance
“…In the present study, no changes were observed in the chlorophyll index after 20 days of the last application of pyraclostrobin + metconazole at R7 (Table 4), corroborating with the results found by Kozlowski et al (2009) in common bean, where there was no change in chlorophyll content one day before, on the day, and 7, 14 and 21 days after a second application of pyraclostrobin, which was also performed at R7.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In the present study, no changes were observed in the chlorophyll index after 20 days of the last application of pyraclostrobin + metconazole at R7 (Table 4), corroborating with the results found by Kozlowski et al (2009) in common bean, where there was no change in chlorophyll content one day before, on the day, and 7, 14 and 21 days after a second application of pyraclostrobin, which was also performed at R7.…”
Section: Resultssupporting
confidence: 80%
“…Nonetheless, contrary results were found for the bean cultivar IPR Uirapuru, for which there was an increase in the number of pods per plant when two applications (V4 and R7) of pyraclostrobin were performed (Kozlowski et al, 2009).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations